2015
DOI: 10.1681/asn.2014040340
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Planar Cell Polarity Protein Vangl2 in Podocytes Affects Glomerular Morphogenesis and Increases Susceptibility to Injury

Abstract: The planar cell polarity (PCP) signaling pathway is crucial for tissue morphogenesis. Van Gogh-like protein 2 (Vangl2) is central in the PCP pathway; in mice, Vangl2 loss is embryonically lethal because of neural tube defects, and mutations in Vangl2 are associated with human neural tube defects. In the kidney, PCP signaling may be important for tubular morphogenesis and organization of glomerular epithelial cells (podocytes) along the glomerular basement membrane. Podocyte cell protrusions (foot processes) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…We reported that although the initiation of the ureteric bud was normal in homozygous mutant Vangl2 embryos, subsequent ureteric bud branching within the metanephros was defective 14 . Furthermore, we 14 and others 15 found that these kidneys contained poorly differentiated glomeruli. These defects correlate with reported sites of Vangl2 mRNA expression, including podocytes and ureteric bud epithelia 14, 16.…”
mentioning
confidence: 67%
“…We reported that although the initiation of the ureteric bud was normal in homozygous mutant Vangl2 embryos, subsequent ureteric bud branching within the metanephros was defective 14 . Furthermore, we 14 and others 15 found that these kidneys contained poorly differentiated glomeruli. These defects correlate with reported sites of Vangl2 mRNA expression, including podocytes and ureteric bud epithelia 14, 16.…”
mentioning
confidence: 67%
“…Podocyte-specific Cre-LoxPmediated abrogation of Vangl2 resulted in a similar glomerular developmental delay phenotype [124]. However, by the end of nephrogenesis at P14, a developmental "catch-up" seems to have occurred so that the glomeruli in either mutant or control mice looked similar, though mutant glomeruli were smaller and had fewer podocytes.…”
Section: Pcp and Glomerular Developmentmentioning
confidence: 90%
“…However, by the end of nephrogenesis at P14, a developmental "catch-up" seems to have occurred so that the glomeruli in either mutant or control mice looked similar, though mutant glomeruli were smaller and had fewer podocytes. Podocyte-specific loss of Vangl2 did not affect filtration function in adult kidneys: protein excretion at 12 months was comparable in both genotypes [124]. Yet, in the context of glomerular injury induced by heterologous anti-glomerular basement membrane (anti-GBM) antibody, the extent of injury was heightened and glomerular recovery was impaired in mutant versus control animals.…”
Section: Pcp and Glomerular Developmentmentioning
confidence: 96%
“…In adult mice, significantly smaller glomeruli were detected, but it did not affect glomerular permselectivity in aging animals. In the context of glomerular injury induced by injection of anti-glomerular basement membrane antibody, deletion of Vangl2 resulted in injury exacerbation and accelerated progression to chronic segmental and global glomerular sclerosis [72,73] (Table 2; Fig. 1).…”
Section: Van Gogh-like Proteinmentioning
confidence: 99%